Parental awareness of rotavirus infection - Burlačenko, Diana; Istomina, Natalja; Truš, Marija (Slauga. Mokslas ir praktika, 2023)
In order to effectively prevent any disease, it is necessary to apply preventive measures in the most vulnerable group of this disease. In the case of rotavirus, it is children. Since parents (guardians) take care of children, their awareness is very important, because only they can ensure the timely vaccination of their children and train them in personal hygiene rules. Rotavirus infection is an urgent public health problem due to the high morbidity in children. In 2022, 93 percent (1462 cases) RVI (rotavirus infection) was recorded among children (0-17 years). In 2018, vaccines against this infection were included in the preventive vaccination calendar for children in Lithuania. Therefore, when applying this RVI prevention measure, it is so important to analyze not only parents' awareness of this disease, but also to evaluate their attitude towards vaccines. Nurses have a significant impact on the prevention of rotavirus infection, as they spend the most time with patients and relatives, to whom they must provide reliable information about the management of the disease and explain the importance of preventive measures. The aim of this study is to analyze parents' awareness of rotavirus infection. Appropriate research methods were chosen during the research: analysis of scientific literature and quantitative research using an anonymous questionnaire (online survey). The research was conducted in accordance with ethical principles. The results revealed that parents lack information about RVI. Only half knew that the main way of spreading the disease is fecal-oral. According to the research data, the majority of parents received information from a reliable source - doctors, and a quarter from nurses. However, the second most frequently cited source is the Internet, which may have provided respondents with false information about the disease and its prevention. Also, according to the research, parents lack knowledge about the formation of children's hygiene skills: the majority of respondents say that education on this issue is necessary. According to scientific literature, the most effective preventive measure against infection is vaccinations, but slightly less than half of the respondents agree that vaccinations are necessary, and a quarter disagree. In addition, when comparing parents' opinions on this issue by education, a significant difference was observed.
Keywords: rotavirus; rotavirus infection; childhood infection; parental awareness